Association between allergic diseases, generalized anxiety disorder, and depressive symptoms in South Korean adolescents: a secondary data analysis of the 2022 Korea Youth Risk Behavior Survey. - Lee, Jaeyoung; Park, So Yeon (Child Health Nursing Research, 2024)
Purpose: This study investigated the relationship between allergic diseases, general anxiety disorder, and depressive symptoms among Korean adolescents. Methods: A secondary analysis was conducted on the findings of the 18th Korea Youth Risk Behavior Survey (2022). The study included 51,850 adolescents and analyzed the relationships among allergic diseases, general anxiety disorder, and depressive symptoms using complex samples logistic regression analysis. Results: Among the Korean adolescents, 12.7% experienced general anxiety disorder, while 28.7% experienced depressive symptoms. The prevalence of allergic diseases was 5.7% for asthma, 36.3% for allergic rhinitis, and 22.2% for atopic dermatitis. General anxiety disorder was associated with asthma and allergic rhinitis but not atopic dermatitis. Depressive symptoms were associated asthma, allergic rhinitis, and atopic dermatitis. Conclusion: Examining the correlation among allergic diseases, general anxiety disorder, and depressive symptoms in adolescents underscores the need for implementing suitable strategies. Moreover, when addressing general anxiety disorder and depressive symptoms in adolescents, it becomes crucial to consider the presence of allergic diseases.